2009
DOI: 10.1108/13673270910997123
|View full text |Cite
|
Sign up to set email alerts
|

Cultural characteristics of knowledge transfer

Abstract: Purpose -In most of the literature, knowledge management is treated as a universal practice, which is transferable from one country or company to another. There are some empirical hints that this is not always the case. The main research question, which this paper aims to answer, is: Which cultural characteristics in Germany and Hong Kong influence knowledge transfer?Design/methodology/approach -A qualitative and exploratory approach has been used to answer the research question. A series of 13 in-depth interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 32 publications
1
62
1
1
Order By: Relevance
“…Previous research has indicated that high power distance cultures tend to prevent effective knowledge sharing because there may be less opportunity for constructive discussions between subsidiaries and HQs (Chen et al, 2010). In addition, Wilkesmann et al (2009) found that in high power distance cultures, knowledge is provided mostly in top down direction and in the bottom up direction only when asked. High power distance has also been referred as a cultural practice which inhibits intrinsic motives for knowledge transfer.…”
Section: Study Propositionsmentioning
confidence: 94%
See 4 more Smart Citations
“…Previous research has indicated that high power distance cultures tend to prevent effective knowledge sharing because there may be less opportunity for constructive discussions between subsidiaries and HQs (Chen et al, 2010). In addition, Wilkesmann et al (2009) found that in high power distance cultures, knowledge is provided mostly in top down direction and in the bottom up direction only when asked. High power distance has also been referred as a cultural practice which inhibits intrinsic motives for knowledge transfer.…”
Section: Study Propositionsmentioning
confidence: 94%
“…Most of such studies explore knowledge transfer between units representing the same national culture (see e.g. Lai and Lee, 2007;Wilkesmann et al, 2009). Therefore, we argue that more systematic analysis of the role of selected cultural characteristic is required; which the current paper aims to perform.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations